"Just as the Structural Formula Does": Names, Diagrams, and the Structure of Organic Chemistry at the 1892 Geneva Nomenclature Congress*. (February 2015) - Hepler-Smith, Evan
<x content-type="archive" xml:space="preserve">Abstract</x> At the Geneva Nomenclature Congress of 1892, some of the foremost organic chemists of the late nineteenth century crafted a novel relationship between chemical substances, chemical diagrams, and chemical names that has shaped practices of chemical representation ever since. During the 1880s, the French chemist Charles Friedel organised the nomenclature reform effort that culminated in the Geneva Congress; in the disorderly nomenclature of German synthetic chemistry, Friedel saw an opportunity to advance French national interests and his own pedagogical goals. Friedel and a group of close colleagues reconceived nomenclature as a unified field, in which all chemical names ought to relate clearly to one another and to the structure of the compounds they represented. The German chemist Adolf von Baeyer went a step farther, arguing for names that precisely and uniquely corresponded to the structural formula of each compound, tailored for use in chemical dictionaries and handbooks. Baeyer's vision prevailed at the Geneva Congress, which consequently codified rules for rigorously mapping structural formulas into names, resulting in names that faithfully represented the features of these diagrams but not always the chemical behaviour of the compounds themselves. This approach ultimately limited both the number of chemical compounds that the Geneva rules were able to encompass and the breadth of their application. However, the relationship between diagram and name established at the Geneva Congress became the foundation not only of subsequent systems of chemical nomenclature but of methods of organising information that have supported the modern chemical sciences.